CAUSES AND PREVENTION OF EPILEPSY. - Amonova Zakhro Kakhramonovna; Niyozov Shukhrat Toshtemirovich; Amonova Zilola Kahramonovna (TADQIQOTLAR.UZ, 2024)
Abstract: Epilepsy is a neurological disorder characterized by recurrent seizures, which are sudden, uncontrolled electrical disturbances in the brain. These seizures can vary in intensity and duration, affecting a person's mind, actions, and emotions. Understanding the causes and taking preventative measures are essential to effectively managing epilepsy.